Urgensi Prinsip Komunikasi Islam dalam Pembelajaran Agama Islam bagi Siswa di Sekolah Umum - Safrawali Safrawali; Fakhrur Rozi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study discusses the urgency of Islamic communication principles in Islamic religious learning for students in public schools. This study wants to see how Islamic communication plays a role in increasing students' understanding of Islamic religious learning in public schools. This study uses a qualitative research method with a descriptive analysis approach. The results of this study indicate that the portrait of Islamic religious learning in public schools is still not optimal. There are at least two factors that cause this to be less than optimal, namely: (1) internal factors originating from within the education management, (2) external factors originating from outside the school management. The application of Islamic communication principles in Islamic religious learning in public schools is still full of challenges, because formally the implementation of Islamic education in schools is only two hours of lessons per week. In addition, the principles of Islamic communication in Islamic religious learning for students in schools get a good response, so that the principles of Islamic communication are very influential for the learning process so that students can be more active and understand PAI learning. Islamic communication can stimulate the response given so that students are more active in this case the role of the teacher is very important and implements various kinds of learning strategies.